PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SYARIAH SEKTOR KESEHATAN DI BEI TAHUN 2016-2020 - Eka Widianti; Rafidah; Nurlia Fusfita (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
This study was conducted with the aim of examining the effect of firm size, leverage, and firm growth on profitability in Islamic health sector companies on the Indonesia Stock Exchange in 2016-2020. This study was tested using 3 independent variables, namely: company size, leverage, and company growth. The dependent variable is profitability. The population used in this study is the health sector Islamic companies listed on the Indonesia Stock Exchange in 2016-2020. The sample used in this study were 50 samples. The analysis used in this study is multiple linear regression and assisted by the Eviews 9 analysis tool. The data used is panel data. The results of this study are that the size of the company partially has a negative and significant effect on profitability, leverage has a positive and significant effect on profitability, while company growth has no effect on profitability. From the results of the simultaneous test company size, leverage, and company growth have an influence on profitability. Keywords: company size, leverage, company growth, profitability.